A high-durability water-based epoxy resin composite waterproof paint for bridge bolt fasteners

CN122381647BActive Publication Date: 2026-11-03HEFEI UNIV OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202610605431.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-05-06
Publication Date
2026-11-03
Estimated Expiration
2046-05-06

AI Technical Summary

Technical Problem

桥梁螺栓安装后至整体涂装前,存在一段露天暴露窗口期,在此期间,螺栓需承受户外高湿、雨露、轻微盐雾等复杂环境侵蚀,而现有防护手段针对性不足,无法适配现场施工工况,存在诸多技术痛点:

Benefits of technology

[0028]1、采用高分子量环氧与低分子量环氧复配体系,低分子量环氧深度渗透发黑氧化膜微孔,与硅烷偶联剂、金属基体形成三元共价键合,高分子量环氧提供高强度成膜,从根源提升界面结合力,避免涂层起皮、脱落。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122381647B_ABST
    Figure CN122381647B_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of waterproof coating, and particularly relates to a high-durability water-based epoxy resin composite waterproof coating for bridge bolt fasteners. The coating is a two-component system, which is composed of a base reinforcing component (containing components A and B) and a composite modified component. Each component is in a specific mass ratio, and the key raw materials include high molecular weight water-based epoxy resin emulsion, water-based modified amine curing agent, silane coupling agent, nano copper oxide, etc. The preparation method sequentially completes the preparation of the base component A, the base component B and the composite modified waterproof coating, and controls specific stirring speed, time and temperature. The coating forms a triple protection system, has good wettability and strong adhesion, low VOC content and good compatibility with subsequent coating layers, can adopt various construction methods, can effectively resist outdoor complex environment erosion, fills the protection blank of the window period of bridge bolt, simplifies the construction process, and is suitable for the window period and long-term protection of bridge bolt fasteners.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of waterproof coating technology, specifically relating to a high-durability waterborne epoxy resin composite waterproof coating for bridge bolt fasteners. Background Technology

[0002] Bridge bolts are core components of bridge structural connections, and their protective performance directly determines the safety and service life of the bridge structure. Between the installation of bridge bolts and the final painting, there is a window of exposure to the elements. During this period, the bolts must withstand the complex environmental corrosion caused by high humidity, rain, dew, and slight salt spray. Existing protective measures are insufficiently targeted and cannot adapt to the specific on-site construction conditions, presenting numerous technical challenges.

[0003] 1) Blackening is a common pretreatment method for bolts. However, the oxide film formed by blackening is thin and has poor density. Under outdoor high humidity, rain, dew and slight salt spray environment, it is prone to pitting and rusting in a short period of time, which cannot meet the protection requirements during the window period.

[0004] 2) Currently, there is no protective coating specifically designed for the window period of bridge bolts. When using general-purpose protective materials, they are prone to peeling off from the subsequent overall coating layer, and some materials are difficult to remove, increasing the construction process and affecting construction efficiency.

[0005] 3) Bridge bolts have irregular structures such as threads, gaps, and sharp corners. Existing coatings have poor wetting properties for these irregular structures, which can easily lead to missed coatings and sagging. Moreover, the coatings are only physically adsorbed to the metal substrate. During construction vibrations or component fine-tuning, the coating is prone to peeling and falling off, and cannot form effective protection.

[0006] 4) Solvent-based coatings have high VOC emissions, which violates relevant regulations on green construction and does not meet environmental protection requirements; while ordinary water-based coating systems have poor stability and weather resistance, and slow film formation speed, which affects the construction progress and cannot meet the construction period requirements of open-air bridge construction.

[0007] 5) The existing coatings do not have good interfacial compatibility with the subsequent epoxy, polyurethane and other overall coating layers of the bridge, which easily leads to delamination and blistering, damaging the overall waterproof and anti-corrosion system and reducing the long-term protective effect of the bolts.

[0008] To address the aforementioned technical challenges, there is an urgent need to develop a specialized waterproof coating for bridge bolts that is highly targeted, adaptable to on-site bridge construction conditions, and possesses environmental friendliness, high adhesion, high density, excellent weather resistance, and coating compatibility. This coating would compensate for the shortcomings of blackening treatment, provide effective protection during the window period, meet long-term protection requirements, simplify construction procedures, and reduce maintenance costs. Summary of the Invention

[0009] The purpose of this invention is to overcome the aforementioned problems in the conventional technology and to provide a high-durability waterborne epoxy resin composite waterproof coating for bridge bolt fasteners.

[0010] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution:

[0011] This invention provides a high-durability waterborne epoxy resin composite waterproof coating, which is a two-component system composed of a basic reinforcing component and a composite modifying component; the basic reinforcing component includes component A and component B, and the components are expressed in parts by weight as follows:

[0012] Basic Component A: 35-50 parts of high molecular weight waterborne epoxy resin emulsion, 3-8 parts of low molecular weight waterborne liquid epoxy resin, 20-30 parts of deionized water, 5-12 parts of zinc phosphate, 0.5-1.5 parts of sodium polycarboxylate dispersant, 0.2-0.6 parts of polyether-modified siloxane, 0.2-0.5 parts of polydimethylsiloxane, and 3-6 parts of epoxy-polyurethane grafted compatibility toughening agent;

[0013] Basic component B: 50-65 parts of water-based modified amine curing agent, 25-40 parts of deionized water, 1-2.5 parts of amphoteric surfactant, and 0.2-0.8 parts of pH adjuster and defoamer;

[0014] Composite modified components: 8-15 parts of basic component A, 15-30 parts of basic component B, 1-2 parts of silane coupling agent, 0.3-1 part of nano copper oxide, 0.5-1.2 parts of modified AlZn alloy powder, and 0.3-0.8 parts of sodium polycarboxylate dispersant.

[0015] Furthermore, the parameters of the high molecular weight waterborne epoxy resin emulsion are as follows: epoxy value 0.18~0.22eq / 100g, solid content 50%±2%, particle size 80~120nm, and Tg 15~25℃.

[0016] Furthermore, the low molecular weight waterborne liquid epoxy resin is waterborne self-emulsifying E-51, with an epoxy value of 0.48 to 0.54 eq / 100g, a solid content of 100%, an epoxy equivalent of 185 to 210 g / eq, and a viscosity of 2000 to 4000 mPa·s at 25°C.

[0017] Furthermore, the water-based modified amine curing agent is a polyether amine with an active hydrogen equivalent of 65-75 g / eq, a solid content of 60% ± 2%, a viscosity of 200-500 mPa·s at 25°C, and a pot life of 4-6 h at 25°C after mixing with component A.

[0018] Furthermore, the nano-copper oxide has a particle size of 20–50 nm; the modified AlZn alloy powder has a particle size of 1 μm, a zinc / aluminum mass ratio of 85 / 15, and an active metal content of ≥98%.

[0019] Furthermore, the sodium polycarboxylate dispersant is model 5040; the amphoteric surfactant is dodecyl dimethyl betaine (BS-12); the pH adjuster is 2-amino-2-methyl-1-propanol (AMP-95); the defoamer is polydimethylsiloxane; and the polyether-modified siloxane is a leveling agent.

[0020] This invention also provides a method for preparing a high-durability waterborne epoxy resin composite waterproof coating, comprising the following steps:

[0021] 1) Preparation of basic component A: Add high molecular weight waterborne epoxy resin emulsion, low molecular weight waterborne liquid epoxy resin and deionized water to a reactor and stir at room temperature for 5-10 min at a speed of 300-500 r / min; add sodium polycarboxylate dispersant and epoxy-polyurethane grafted compatibility toughening agent and stir for 3-5 min for pre-compatibility; add zinc phosphate, polyether modified siloxane and polydimethylsiloxane in sequence, stirring for 5-8 min after each addition; increase the speed to 800-1000 r / min and disperse at high speed for 15-20 min, then seal and protect from light for later use.

[0022] 2) Preparation of basic component B: Add the water-based modified amine curing agent and deionized water to the reactor and stir at room temperature at a speed of 200-300 r / min for 3-5 min; add the amphoteric surfactant and stir for 5-8 min until completely dissolved; add the pH adjuster and defoamer, stir for 3-5 min, adjust the pH of the system to 7.5-8.5, and seal and protect from light for later use;

[0023] 3) Preparation of composite modified waterproof coating: Mix the base component A with sodium polycarboxylate dispersant and stir at 800-1000 r / min for 5 min. Then, add nano copper oxide and modified AlZn alloy powder in sequence, increase the speed to 1000-1200 r / min, and disperse at high speed for 20-30 min to obtain a composite slurry. Add a silane coupling agent to the composite slurry, reduce the speed to 600-800 r / min, and stir for 10-20 min. Control the pH of the system to 4.0-5.0 and the temperature to 25-35℃ to allow the silane coupling agent to fully hydrolyze and pre-bond. Add the base component B, adjust the speed to 300-500 r / min, and stir at room temperature for 5-10 min. Mix evenly to obtain the finished waterproof coating.

[0024] Furthermore, in step 1), the high-speed dispersion temperature is ≤45℃ to prevent the system from demulsifying.

[0025] Furthermore, in step 3), the pH of the system is finely adjusted to 4.0–5.0 using acetic acid.

[0026] This invention also provides an application of a high-durability waterborne epoxy resin composite waterproof coating in the protection of bridge bolt fasteners.

[0027] The beneficial effects of this invention are:

[0028] 1. A high molecular weight epoxy and low molecular weight epoxy compound system is adopted. The low molecular weight epoxy deeply penetrates the micropores of the black oxide film and forms a ternary covalent bond with the silane coupling agent and the metal matrix. The high molecular weight epoxy provides high-strength film formation, which improves the interfacial bonding force from the source and avoids coating peeling and flaking.

[0029] 2. A triple protection system of "chemical reinforcement layer + dense shielding layer + sacrificial anode protection" is formed. After testing, no rust was found in the 120-hour neutral salt spray test, filling the gap in bridge bolt protection technology during the window period and effectively resisting corrosion in complex outdoor environments.

[0030] 3. The silane coupling agent and amphoteric surfactant work synergistically to improve the wettability of the coating, and the nano copper oxide fills the threads, gaps and other parts, with almost zero missed coating rate for threads and sharp corners, ensuring that all parts of the bolt are effectively protected.

[0031] 4. Epoxy-polyurethane grafted toughening agents enable the coating to form an interpenetrating interface with subsequent epoxy, polyurethane, and other integral coating layers, resulting in high adhesion, no interlayer peeling or blistering, no need for additional coating removal, simplified construction procedures, and improved construction efficiency.

[0032] 5. Two-component water-based system with VOC content ≤28g / L, meeting green construction standards and causing no environmental pollution; flexible construction methods, including brushing, dipping, and spraying; rapid film formation at room temperature; stable outdoor storage; no special equipment required; suitable for outdoor construction and project schedule requirements.

[0033] 6. Through the synergistic effect of electrostatic adsorption, electrostatic repulsion, and electrostatic wetting, a strong interfacial bond is achieved between the coating and the blackening layer and the metal substrate. The filler is evenly dispersed and does not settle, and irregular parts are fully wetted without dead corners, further improving the coating adhesion, construction uniformity, and long-term protective reliability.

[0034] Of course, any product implementing this invention does not necessarily need to achieve all of the above advantages at the same time. Attached Figure Description

[0035] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0036] Figure 1This is a schematic diagram of the interface between the coating and the bridge bolts in this embodiment;

[0037] Figure 2 This is a schematic diagram illustrating the effect of coating on the irregular structure (threads / gaps) of the bridge bolts after coating in this embodiment;

[0038] Where a represents individual bolts and nuts after coating, and b represents bolts and nuts assembled after coating. Detailed Implementation

[0039] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0040] Example 1

[0041] This embodiment describes a waterproof coating for conventional highway bridge bolts. The coating formula (by weight parts) is as follows:

[0042] Basic Component A: 40 parts high molecular weight waterborne epoxy resin emulsion, 5 parts low molecular weight waterborne liquid epoxy resin (E-51), 25 parts deionized water, 8 parts zinc phosphate, 1 part sodium polycarboxylate dispersant (5040), 0.3 parts polyether modified siloxane, 0.3 parts polydimethylsiloxane, and 4 parts epoxy-polyurethane grafted compatibility toughening agent;

[0043] Basic Component B: 60 parts of water-based modified amine curing agent (polyether amine), 30 parts of deionized water, 2 parts of amphoteric surfactant (BS-12), 0.5 parts of pH adjuster (AMP-95) and defoamer;

[0044] Composite modified components: 10 parts of basic component A, 20 parts of basic component B, 1.5 parts of silane coupling agent (KH-560), 0.6 parts of nano copper oxide, 0.8 parts of modified AlZn alloy powder, and 0.5 parts of sodium polycarboxylate dispersant (5040).

[0045] The preparation method is as follows:

[0046] 1) Preparation of basic component A: Add 40 parts of high molecular weight waterborne epoxy resin emulsion, 5 parts of low molecular weight waterborne liquid epoxy resin and 25 parts of deionized water to a reactor and stir at 300-500 r / min at room temperature for 5-10 min; add 1 part of sodium polycarboxylate dispersant and 4 parts of compatibility toughening agent, and stir for 3-5 min for pre-compatibility; add 8 parts of zinc phosphate, 0.3 parts of polyether modified siloxane and 0.3 parts of polydimethylsiloxane in sequence, stirring for 5-8 min after each addition; increase the speed to 800-1000 r / min for high-speed dispersion for 15-20 min, control the dispersion temperature ≤45℃, and seal and protect from light for later use;

[0047] 2) Preparation of basic component B: Add 60 parts of water-based modified amine curing agent and 30 parts of deionized water to the reactor, stir at 200-300 r / min at room temperature for 3-5 min; add 2 parts of BS-12, stir for 5-8 min until dissolved; add 0.5 parts of AMP-95 and defoamer, stir for 3-5 min, adjust the pH to 7.5-8.5, seal and protect from light for later use;

[0048] 3) Preparation of composite modified waterproof coating: Mix 10 parts of base component A with 0.5 parts of sodium polycarboxylate dispersant, stir at 800-1000 r / min for 5 min, add 0.6 parts of nano copper oxide and 0.8 parts of modified AlZn alloy powder in sequence, and disperse at 1000-1200 r / min for 20-30 min to obtain composite slurry; add 1.5 parts of KH-560 to composite slurry, reduce to 600-800 r / min and stir for 10-20 min, adjust pH to 4.0-5.0 with acetic acid, control temperature at 25-35℃, and fully hydrolyze and pre-bond; add 20 parts of base component B, adjust to 300-500 r / min and stir at room temperature for 5-10 min, mix evenly to obtain the finished product.

[0049] To protect carbon steel bolts that have undergone conventional blackening treatment on highway bridges, follow these steps:

[0050] 1) Substrate pretreatment: Remove surface dust, oxide powder, and oil from the bolts, retaining the blackened oxide film; lightly grind the threads and sharp corner burrs; rinse with deionized water, air dry in cold air, and complete the coating within 24 hours;

[0051] 2) Coating: Dip coating is used. After dip coating, centrifuge at 500-600 r / min for 30-60 s to control the dry film thickness to 15 μm.

[0052] 3) Curing: Curing in a well-ventilated environment with a temperature of 25℃ and a humidity of 60% for 25 minutes to surface dry and 3.5 hours to fully dry.

[0053] Performance test results: 120h neutral salt spray test grade 0 (no rust, no pitting, no blistering); adhesion grade 0 (cross-cut test, no peeling); VOC content 26g / L, meeting green construction requirements; thread coverage 100%, no missed coating; good compatibility with subsequent polyurethane coating layers, no delamination or blistering.

[0054] Example 2

[0055] This embodiment describes a waterproof coating for high salt spray resistance bridge bolts in coastal areas. The coating formula (by weight parts) is as follows:

[0056] Basic Component A: 45 parts high molecular weight waterborne epoxy resin emulsion, 5 parts low molecular weight waterborne liquid epoxy resin (E-51), 22 parts deionized water, 10 parts zinc phosphate, 1.2 parts sodium polycarboxylate dispersant (5040), 0.4 parts polyether modified siloxane, 0.4 parts polydimethylsiloxane, and 5 parts epoxy-polyurethane grafted compatibility toughening agent;

[0057] Basic Component B: 65 parts of water-based modified amine curing agent (polyetheramine), 28 parts of deionized water, 2.2 parts of amphoteric surfactant (BS-12), 0.6 parts of pH adjuster (AMP-95) and defoamer;

[0058] Composite modified components: 12 parts of basic component A, 25 parts of basic component B, 1.8 parts of silane coupling agent (KH-560), 0.8 parts of nano copper oxide, 1.0 part of modified AlZn alloy powder, and 0.6 parts of sodium polycarboxylate dispersant (5040).

[0059] Preparation method: Same as in Example 1, only the dosage of each component and some parameters are adjusted, wherein the high-speed dispersion time of basic component A is 20 min, and the high-speed dispersion time of composite slurry is 30 min.

[0060] For the protection of bridge alloy steel bolts with high salt spray resistance requirements along the coast, the coating method is spraying, with the spray gun distance controlled at 15-20cm, pressure at 0.3-0.5MPa, and dry film thickness at 17μm; the curing conditions are temperature at 30℃, humidity at 70%, surface drying at 28min, and complete drying at 3.8h.

[0061] Performance test results: 148h neutral salt spray test grade 0; adhesion grade 0; interlayer compatibility grade 0 (when used with epoxy micaceous iron oxide intermediate paint + aliphatic polyurethane topcoat, no delamination or blistering); VOC content 27g / L; thread coverage 100%.

[0062] Example 3

[0063] This example describes a waterproof coating for bridge bolts used in low-temperature construction in northern regions. The coating formula (by weight) is as follows:

[0064] Basic Component A: 35 parts high molecular weight waterborne epoxy resin emulsion, 5 parts low molecular weight waterborne liquid epoxy resin (E-51), 28 parts deionized water, 7 parts zinc phosphate, 0.8 parts sodium polycarboxylate dispersant (5040), 0.5 parts polyether modified siloxane, 0.4 parts polydimethylsiloxane, and 3.5 parts epoxy-polyurethane grafted compatibility toughening agent;

[0065] Basic Component B: 55 parts of water-based modified amine curing agent (polyetheramine), 35 parts of deionized water, 1.5 parts of amphoteric surfactant (BS-12), 0.4 parts of pH adjuster (AMP-95) and defoamer;

[0066] Composite modified components: 9 parts of basic component A, 18 parts of basic component B, 1.2 parts of silane coupling agent (KH-560), 0.5 parts of nano copper oxide, 0.7 parts of modified AlZn alloy powder, and 0.4 parts of sodium polycarboxylate dispersant (5040).

[0067] Preparation method: Same as in Example 1, only the amount of each component is adjusted. The temperature of the composite slurry is controlled at 30°C during stirring to ensure that the silane coupling agent is fully hydrolyzed.

[0068] For bridge bolts constructed in low-temperature environments in northern regions, protection is provided by using 40-50℃ hot air for drying during curing. The temperature is 5℃, the humidity is 80%, the surface drying time is 28 minutes, the complete drying time is 1.8 hours, and the dry film thickness is 14μm.

[0069] Performance test results: 136h neutral salt spray test grade 0; adhesion grade 1; VOC content 24g / L; thread coverage 100%; suitable for low-temperature construction conditions, with good film formation effect.

[0070] Comparative test

[0071] To verify the superiority of the coating of the present invention, a blank sample, Comparative Example 1 (commercially available ordinary water-based epoxy coating), Comparative Example 2 (commercially available solvent-based epoxy anti-corrosion coating) and the coating of the present invention (Example 1) were compared for performance. The test results are shown in Table 1 below:

[0072] Table 1

[0073]

[0074] Note: All performance tests are conducted in accordance with the corresponding national standards: adhesion is in accordance with GB / T 5210–2006, neutral salt spray is in accordance with GB / T 10125–2021, VOC content is in accordance with GB 30981–2020, and interlayer compatibility is tested using the matching epoxy micaceous iron oxide intermediate paint + aliphatic polyurethane topcoat, with grade 0 being qualified.

[0075] The comparative test results show that the coating of the present invention is superior to commercially available ordinary water-based epoxy coatings and solvent-based epoxy anti-corrosion coatings in terms of salt spray resistance, adhesion, interlayer compatibility, environmental friendliness, and workability. It can effectively solve the technical pain points of bridge bolt window period protection, adapt to bridge on-site construction conditions, and has significant technical advantages and application value.

[0076] from Figure 1 It is clearly visible that the coating is tightly bonded to the substrate and the blackened oxide film, with a uniform thickness of approximately 14 μm and no obvious defects. Figure 2 As can be seen, the root of the bolt thread, the side of the thread, and the joint of the washer are all completely covered by the coating, without bubbles or missed coating. The coating thickness is uniform and consistent, and the edge transition is smooth without material accumulation, which fully demonstrates the good coverage of the coating of the present invention on irregular structures.

[0077] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A high-durability waterborne epoxy resin composite waterproof coating for bridge bolt fasteners, characterized in that, It is a two-component system, consisting of a basic reinforcing component and a composite modifying component; the basic reinforcing component includes component A and component B, and the components are expressed in parts by mass as follows: Basic Component A: 35-50 parts of high molecular weight waterborne epoxy resin emulsion, 3-8 parts of low molecular weight waterborne liquid epoxy resin, 20-30 parts of deionized water, 5-12 parts of zinc phosphate, 0.5-1.5 parts of sodium polycarboxylate dispersant, 0.2-0.6 parts of polyether-modified siloxane, 0.2-0.5 parts of polydimethylsiloxane, and 3-6 parts of epoxy-polyurethane grafted compatibility toughening agent; the parameters of the high molecular weight waterborne epoxy resin emulsion are: epoxy value 0.18-0.22 eq / 100g, solid content 50%±2%, particle size 80-120nm, Tg The temperature range is 15–25°C; the low molecular weight waterborne liquid epoxy resin is waterborne self-emulsifying E-51, with an epoxy value of 0.48–0.54 eq / 100g, a solid content of 100%, an epoxy equivalent of 185–210 g / eq, and a viscosity of 2000–4000 mPa·s at 25°C; the polyether-modified siloxane is used as a leveling agent. Basic Component B: 50-65 parts of water-based modified amine curing agent, 25-40 parts of deionized water, 1-2.5 parts of amphoteric surfactant, and 0.2-0.8 parts of pH adjuster and defoamer; the water-based modified amine curing agent is polyether amine, with an active hydrogen equivalent of 65-75 g / eq, a solid content of 60% ± 2%, a viscosity of 200-500 mPa·s at 25°C, and a pot life of 4-6 h at 25°C after mixing with Component A; the amphoteric surfactant is dodecyl dimethyl betaine; the pH adjuster is 2-amino-2-methyl-1-propanol; and the defoamer is polydimethylsiloxane. Composite modified components: 8-15 parts of basic component A, 15-30 parts of basic component B, 1-2 parts of silane coupling agent, 0.3-1 part of nano copper oxide, 0.5-1.2 parts of modified AlZn alloy powder, and 0.3-0.8 parts of sodium polycarboxylate dispersant; the nano copper oxide has a particle size of 20-50 nm; the modified AlZn alloy powder has a particle size of 1 μm, a zinc / aluminum mass ratio of 85 / 15, and an active metal content ≥98%; the sodium polycarboxylate dispersant is model 5040.

2. The preparation method of the high-durability waterborne epoxy resin composite waterproof coating as described in claim 1, characterized in that, Includes the following steps: 1) Preparation of basic component A: Add high molecular weight waterborne epoxy resin emulsion, low molecular weight waterborne liquid epoxy resin and deionized water to a reactor and stir at room temperature for 5-10 min at a speed of 300-500 r / min; add sodium polycarboxylate dispersant and epoxy-polyurethane grafted compatibility toughening agent and stir for 3-5 min for pre-compatibility; add zinc phosphate, polyether modified siloxane and polydimethylsiloxane in sequence, stirring for 5-8 min after each addition; increase the speed to 800-1000 r / min and disperse at high speed for 15-20 min, then seal and protect from light for later use. 2) Preparation of basic component B: Add the water-based modified amine curing agent and deionized water to the reactor and stir at room temperature at a speed of 200-300 r / min for 3-5 min; add the amphoteric surfactant and stir for 5-8 min until completely dissolved; add the pH adjuster and defoamer, stir for 3-5 min, adjust the pH of the system to 7.5-8.5, and seal and protect from light for later use; 3) Preparation of composite modified waterproof coating: Mix the base component A with sodium polycarboxylate dispersant and stir at 800-1000 r / min for 5 min. Then add nano copper oxide and modified AlZn alloy powder in sequence, increase the speed to 1000-1200 r / min, and disperse at high speed for 20-30 min to obtain composite slurry. Add silane coupling agent to composite slurry, reduce the speed to 600-800 r / min, stir for 10-20 min, and control the pH of the system to 4.0-5.0 and the temperature to 25-35℃ to allow the silane coupling agent to be fully hydrolyzed and pre-bonded. Add the base component B, adjust the speed to 300-500 r / min, stir at room temperature for 5-10 minutes, and the finished waterproof coating is obtained when it is mixed evenly.

3. The preparation method according to claim 2, characterized in that, In step 1), the high-speed dispersion temperature should be ≤45℃ to prevent the system from demulsifying.

4. The preparation method according to claim 3, characterized in that, In step 3), the pH of the system is fine-tuned to 4.0–5.0 using acetic acid.

5. The application of the high-durability waterborne epoxy resin composite waterproof coating as described in claim 1 in the protection of bridge bolt fasteners.

Citation Information

Patent Citations

  • Waterborne epoxy primer-topcoat paint for stainless steel base material and preparation method thereof

    CN111040570A

  • Modified polyaniline synergistic flaky zinc-aluminum waterborne epoxy anticorrosive paint and preparation method thereof

    CN121022216A